An Investigation Into the Reuse of Organic Waste Produced by the New Zealand Mussel Industry - Barnaby, Claire (Auckland University of Technology, 2004)
Management of organic waste is a major problem for the New Zealand Mussel Industry. Currently most waste is discarded, and this represents a potential loss of both resources and revenue, unless an alternative use for this waste could be developed. Waste types were first identified, then quantified, first seasonally, then annually, to provide an estimate of total industry-wide waste production. Possible uses for this waste were then identified. Little investigative research has been undertaken on identifying alternative uses for mussel industry organic waste. The uses of organic waste as organic fertilizers, and the economic benefit of adding treated waste products to cement mix to improve its compressive strength and thermal insulation, are two primary objectives of this dissertation. The possibility of using mussel shell in agricultural liming as a substitute is also explored. The potential value of pre-grade waste as an organic fertilizer was explored by addition of decomposed tissue to tomato seedlings and by monitoring plant development and condition. Growth of treatment and control seedlings was monitored by counting the number of branches, stem heights, leaf numbers and total biomass. Analyses prove Perna canaliculus pre-grade organic waste has the potential to be exploited as an expensive, effective organic fertilizer, whereas Mytilus galloprovincialis pre-grade organic waste may not. Moreover, there is further potential to develop P. canaliculus pre-grade organic waste into an odourless, chemically stable fertilizer product. The potential value of post-grade waste in cement mixes to improve compressive strength was explored by addition of shell aggregate to cement mix. Analyses indicate that, as an aggregate, mussel shell has little to no structural potential, but does have latent thermal insulating properties. Recommendations are made to: - Separate Perna and Mytilus pre-grade waste products. - Further explore the thermal insulating potential of mussel-shell concrete. - Further explore techniques for treatment of Perna pre-grade waste as a fertilizer. - Further explore the use of crushed mussel shell as a potential limestone or sand substitute for agricultural, construction and engineering purposes. - Explore markets for Mytilus potential export, to reduce pre-grade waste production and problems of resettlement.
Keywords: Mussel fisheries; Environmental studies